Acoustical investigation of ambience sound for auditory environments in music performance spaces. (October 2016) - Park, Hocheul; Jeon, Jin Yong
Abstract: The optimal array pattern and height for ambience recording were investigated in a performance space through the use of microphone arrays, such as the Hamasaki-square, IRT-Cross, and Omni-square. The optimal array pattern was selected based on evaluations of ambient recorded sounds for subjective attributes such as spaciousness, envelopment, naturalness, balance, stereo compatibility, and overall preference. Then these attributes were compared with acoustical parameters such as clarity (C80), the inter-channel cross-correlation coefficient (ICCC), and the number of peaks (Np) from the measured room impulse responses. In addition, as an assessment of the optimal height of the array, auditory perception was evaluated with the method of paired comparisons. The results showed that the Hamasaki-square, which exhibited lower C80 and ICCC values and higher Np values, was preferred in the subjective listening test. It was also revealed that the listeners' preferred height was characterized by uniformly distributed ambience sounds with low C80 value and small deviation for the early decay time (EDT), sound pressure level (SPL), Np, and C80. Highlights: Ambience techniques and optimal array heights were investigated both subjectively and objectively. Array preferences were correlated with naturalness, balance, spaciousness, and envelopment. Highly rated array pattern obtained lower C80 and ICCC values, as well as higher Np values. The optimal array height had a uniformly distributed auditory image in the hall.